2011
DOI: 10.1016/j.taap.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of developmentally toxic drinking water disinfection byproducts and evaluation of data relevant to mode of action

Abstract: Reactions between chemicals used to disinfect drinking water and compounds present in source waters produce chemical mixtures containing hundreds of disinfection byproducts (DBPs). Although the results have been somewhat inconsistent, some epidemiological studies suggest associations may exist between DBP exposures and adverse developmental outcomes. The potencies of individual DBPs in rodent and rabbit developmental bioassays suggest that no individual DBP can account for the relative risk estimates reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 122 publications
(406 reference statements)
1
21
0
Order By: Relevance
“…Epidemiological research demonstrated low but significant associations between disinfected drinking water and adverse health effects (10) including cancer of the bladder (14)(15)(16), colon (17,18) and rectum (19). Some studies report a weak association with adverse pregnancy outcomes and DBPs; yet, the evidence is inconclusive (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological research demonstrated low but significant associations between disinfected drinking water and adverse health effects (10) including cancer of the bladder (14)(15)(16), colon (17,18) and rectum (19). Some studies report a weak association with adverse pregnancy outcomes and DBPs; yet, the evidence is inconclusive (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologic studies have reported associations between THM exposure and bladder cancer (Villanueva et al 2004, 2007). There is compelling evidence of associations between THM exposure and preterm delivery and small for gestational age/intrauterine growth restriction, but evidence for other reproductive/developmental outcomes remains inconsistent (Colman et al 2011; Nieuwenhuijsen et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Elucidating the potential impact of exposure to brominated THMs remains a key research need because they are more potent toxicants than TCM. 21,22 In this study, previous analyses from 1995 to 1998 15 have been extended to 1996 to 2004 to examine associations between exposure to individual and summary measures of THMs and HAAs with birth weight (BWT), SGA, and PTD. This large data set allowed for an assessment of low and unexposed reference groups and also provided sufficient exposure gradients to examine the brominated THMs.…”
mentioning
confidence: 99%